Agrobacterium-mediated Transformation and Constitutive Expression of PgNHX1 from Pennisetum glaucum L. in Oryza sativa L. cv. Binnatoa (Plant Tissue Culture and Biotechnology, 2010)
In an effort to improve salinity tolerance in rice, the Pennisetum glaucum vacuolar Na+/H+ antiporter gene (PgNHX1) was transformed and expressed in Bangla-deshi rice Binnatoa under the constitutive promoter CaMV35S. Transgenic status of the plant was confirmed by PCR and Southern blot hybridization. RT-PCR and Western dot-blot analyses were performed to validate the expression of the transgene at RNA and protein levels, respectively. At 160 mM (ECe of 16 dS/m) NaCl stress the transgenic seedlings showed enhanced tolerance compared to controls. Key words:  Salinity tolerance, PgNHX1, CaMV35S, Binnatoa D.O.I.10.3329/ptcb.v19i1.4912 Plant Tissue Cult. & Biotech. 19(1): 25-33, 2009 (June)